Pengaruh Kompensasi, Iklim Kerja, dan Kepemimpinan Terhadap Kepuasan Kerja dan Kinerja Karyawan - Manner Tampubolon (CERED Indonesia Institute, 2021)
This study aims to analyze the effect of compensation, leadership, and work climate on employee performance mediated by job satisfaction. This study uses a descriptive quantitative approach with data sourced from 284 respondents obtained by survey techniques using a questionnaire. The data is analyzed with a Path Analysis approaches helped by SmartPLS. The results of this study indicate that compensation, leadership and organizational climate directly affect Job Satisfaction. Compensation and leadership also have a direct influence on employee performance, but the work climate has no effect on employee performance. Compensation, leadership and work climate have a direct effect on employee performance. Meanwhile, job satisfaction only acts as a mediating variable on the effect of compensation on employee performance.